Energy levels of natural sensitizers extracted from rengas (Gluta spp.) and mengkulang (Heritiera elata) wood for dye-sensitized solar cells - Safie, Nur Ezyanie; Ahmad Ludin, Norasikin; Hamid, Norul Hisham; Sepeai, Suhaila; Mat Teridi, Mohd Asri; Ibrahim, Mohd Adib; Sopian, Kamaruzzaman; Arakawa, Hironori (SpringerOpen, 2017)
Dye-sensitized solar cells (DSSCs) are fabricated using natural sensitizers extracted from rengas (Gluta spp.) and mengkulang (Heritieraelata) wood. The natural sensitizers are extracted using a cold extraction and the Soxhlet extraction methods. This paper presents the results of the analysis of the optical characteristics of the sensitizers via ultraviolet–visible spectrophotometry and Fourier transform infrared spectroscopy. The optical band gap and the highest occupied molecular orbital (HOMO)–lowest unoccupied molecular orbital (LUMO) levels of each investigated sensitizer are calculated on the basis of the analyzed data collected from photoluminescence and cyclic voltammetry. The DSSCs with the mengkulang sensitizer have better conversion efficiency (ŋ = 0.1695%) than the DSSCs with the rengas sensitizer (ŋ = 0.109%). The performance of the DSSCs indicates an increment as the ratios of the mixed mengkulang:rengas (60%:40%) and mengkulang:rengas (40%:60%) sensitizers increase up to 0.296 and 0.292%, respectively.